Ceratoconjuntivite nodular em um caso de leishmaniose visceral canina: Relato de caso - Eguchi, G. U.; Oliveira, G. G.; Babo-Terra, V. J.; Souza, A. I.; Barros, R. [UNESP]; Palumbo, M. I.P. (FapUNIFESP (SciELO), 2017)
We describe a case of canine visceral leishmaniasis with nodular keratoconjunctivits as the owner's only complaint. Diagnosis was made by the observation of Leishmania sp. amastigotes in parasitological examination from conjunctival aspirative cytology. Eye lesions are rarely the only complaint of dogs suspected of leishmaniasis, as the case reported, demonstrating the variability of clinical presentation of the disease and the importance of performing screening diagnostic laboratorial tests for leishmaniasis in endemic areas.
Nodular keratoconjunctivitis in a case of canine visceral leishmaniasis: Case report
Keywords: Eye diseases; Leishmania; Neoplasms